Genetic evolutionary aspects of Nucleoprotein (N) and Fusion (F) gene of circulating Peste des Petits Ruminants (PPR) virus in Bangladesh - Sajeda Sultana; Nazneen Sultana; Munmun Pervin; Dilruba Parvin; Md Mominul Islam; Mohammad Abu Hadi Noor Ali Khan (Research in Agriculture Livestock and Fisheries, 2025)
This study aimed to understand the genetic evolutionary aspects of the circulating PPRV in Bangladesh using sequence and phylogenetic analysis. 18 samples of N gene and 7 samples of F gene of PPRV isolates were sequenced from a commercial source (Macrogen, Korea). CLC sequence viewer 8 and ExPasy Protein translation tools were used for analysis. The PPRV isolates from the years 2008 and 2015 in Bangladesh were used for comparative genetic analysis of study isolates. The N gene of PPRV (18 isolates) nucleotide analysis revealed that the nucleotide divergence highest was 3-6% and only 1-3% when aligned with BD-2008/MG581412 and BD-2015/OK274192 isolates, respectively. The mutation of N gene of PPRV is slow but continuously evolved. The F gene of PPRV (7 isolates) nucleotide sequence analysis revealed that the nucleotide divergence was only 1-2% when aligned with both (MG581412/2008) and (UQW80114/2015), which remained unchanged from 2008 to 2021. The amino acids divergence of N gene and F gene were 0-11% and 0-2%, respectively. The F gene is relatively more conserved than the N gene of PPRV. The highest homology of N gene sequences with China isolates (98.19%) and the F gene sequences with India isolates (99.29%), respectively, and genetically belong to Lineage IV. The similarity of the studied N gene (94-99%) and F gene isolates (98-99%) among other Bangladeshi isolates made quite a distinct and separate subcluster. The knowledge from such studies will aid in attaining the goal of managing and eradicating the PPR disease from the country. Res. Agric. Livest. Fish. Vol. 11, No. 3, December 2024: 283-294